Wrestling with Democracy : Voting Systems as Politics in the 20th Century West. - Pilon, Dennis (University of Toronto Press, 2013)
Using a comparative historical approach, Wrestling with Democracy examines why voting systems have (or have not) changed in western industrialized countries over the past century.